PENGARUH PEMAHAMAN, KESADARAN DAN PERSEPSI WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI PENSIUNAN PEGAWAI NEGERI TERKAIT ADANYA PELAKSANAAN TAX AMNESTY (STUDI KASUS DI KANTOR PELAYANAN PAJAK PRATAMA BEKASI BARAT) - Hj. Dewi Rejeki, SE., Ak., M.Si., CA. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2017)
This study was conducted to determine the effect simultaneously and partially between Understanding, Awareness and Perception of Taxpayers to Personal Taxpayer Compliance related to the implementation of Tax Amnesty in Tax Office Pratama West Bekasi.This research was conducted in Primary Tax Service Office in West Bekasi. The method used for data collection is survey through primary data. The method of analysis used is a quantitative approach.Research result Shows that simultaneously, the awareness and perception of the taxpayer has a significant and positive influence on the Taxpayer Personal Compliance Personnel related to the implementation of Tax Amnesty and the result partially indicates that the variable of Taxpayer's Values, Awareness and Perception on the Compliance of the Personal Taxpayer of Retired Civil Servant Related to the implementation of Tax Amnesty, where the three factors contribute to the taxpayer Personal Compliance variable of Pensioners of the State Administration related to the implementation of Tax Amnesty of 38.1%.